FBXO2 Promotes Proliferation of Endometrial Cancer by Ubiquitin-Mediated Degradation of FBN1 in the Regulation of the Cell Cycle and the Autophagy Pathway - Che, Xiaoxia; Jian, Fangfang; Wang, Ying; Zhang, Jingjing; Shen, Jian; Cheng, Qi; Wang, Xi; Jia, Nan; Feng, Weiwei (Frontiers in Cell and Developmental Biology, 2020)
F-box proteins, as substrates for S phase kinase-associated protein 1 (SKP1)-cullin 1 (CUL1)-F-box protein (SCF) ubiquitin ligase complexes, mediate the degradation of a large number of regulatory proteins involved in cancer processes. In this study, we found that F-box only protein 2 (FBXO2) was up-regulated in 21 endometrial carcinoma (EC) samples compared with 5 normal endometrium samples based on our Fudan cohort RNA-sequencing. The increased FBXO2 expression was associated with tumor stage, tumor grade, and histologic tumor type, and poor prognosis based on the Cancer Genome Atlas (TCGA) database. FBXO2 knockdown inhibited EC cell proliferation, and FBXO2 overexpression promoted the parental cell phenotype in vivo and in vitro. Fibrillin1 (FBN1) was also identified as a substrate for FBXO2 using a ubiquitination-proteome approach. In addition, promotion of EC proliferation by FBXO2 was regulated by specific proteins of the cell cycle (CDK4, CyclinD1, CyclinD2, and CyclinA1) and the autophagy signaling pathway (ATG4A and ATG4D) based on RNA sequencing. We concluded that FBXO2 acts as an E3 ligase that targets FBN1 for ubiquitin-dependent degradation, so as to promote EC proliferation by regulating the cell cycle and the autophagy signaling pathway. Targeting FBXO2 may represent a potential therapeutic target for EC.